Aggressive adenomatoid odontogenic tumor: an uncommon case report and discussion on the differential diagnosis - Cunha, John Lennon Silva; Fonte, Juliana Batista Melo da; de-Melo, Maria de Fátima Batista; Pereira Filho, Rose Nely; Albuquerque Júnior, Ricardo Luiz Cavalcanti de (Journal of Oral Diagnosis, 2018)
Differential diagnosis between ameloblastomas (AMB) and adenomatoid odontogenic tumor (AOT) seldom cause difficulties due to classic histopathological presentations. Adenoid ameloblastoma with dentinoid (AAD) is a rare variant of AMB which can be misdiagnosed as AOT. We report a case of a 12-year-old female presenting a painless swelling in the anterior region of the mandible. Panoramic radiograph and cone beam CT scans demonstrated large unilocular osteolytic lesion extending from 44 to 32 and involving the impacted 43. Tumor caused teeth displacement and both vestibular and lingual cortical perforation. Histopathology revealed cuboidal and spindle-shaped cells arranged in nests and rosettes, solid, duct-like and whorled areas, and foci of calcification and dentin-like material were evident. The diagnosis was aggressive AOT. Because of the similarities of the histologic features of AOT and AAD, we intend to provide a discussion on the clinicopathologic criteria for establishing the differential diagnosis of these entities